'Birthing a Better Future': A mixed‐methods evaluation of an exhibition on the early years of life - Maya Lakhanpaul; Emma C. Alexander; Meghan A. Cupp; Jessica Taripre Owugha; Alex Florschutz; Andy Beckingham; Virad Kisan; Monica Lakhanpaul; Logan Manikam (Wiley, 2021)
Abstract Background Our study aimed to evaluate to what extent Zero2 Expo's 'Birthing a Better Future', a co‐created multimedia exhibition, was effective in raising awareness on the importance of the first 1001 days of life and explore what refinements would help to optimize the impact of future exhibitions. Methods We conducted a mixed‐methods evaluation of the exhibition delivered in the John Radcliffe Hospital, Oxford. Through convenience sampling, 14 participants were selected to participate in 12 structured interviews and 19 participants completed a questionnaire. Interviews were thematically analysed alongside quantitative analysis of questionnaire responses through Likert scales. Results The majority (78.6%, n = 11/14) of participants who completed the questionnaire either agreed or strongly agreed that the exhibition raised their awareness about the first 1001 days of life. This was supported by the analysis of interviews. The use of art was found to provoke an emotional engagement from participants. Participants felt that the length of the written pieces and location of the exhibition were important factors for designers to consider in future exhibitions. Conclusion This study demonstrated that multimedia exhibitions, combining science with art, may be an effective way to raise awareness of public health messages. Engaging with key stakeholders will be an essential step in order to improve future public health exhibitions. Public Contribution When designing the study, the public reviewed the study tools, which were refined based on their feedback. At every phase of the study, members of the public who are artists co‐created the exhibition content.